Ultrasonic reflection mode tomography using frequency-shift method - Tosranon, P.; Onemanisone, T.; Greesuradej, P.; Pintavirooj, C.; Jaruwongrungsee, K. (My University, 2006)
Tomogram of the soft tissue can be reconstructed by using its projections resolved from the ultrasonic broadband pulsed waves which are passed through the tissue. While a data from ultrasonic transmission mode tomography cannot be used to image the character of soft tissue where shadowed by a bone, an ultrasonic reflection mode tomography is realized to be a solution for this. There are many ways to extract the projections, in most case the integrated attenuation coefficients of the tissue from the pulsed wave. Almost all of these methods were proved to implement with the transmission mode signal, but however, some adaptation may takes benefit from those method to implement with the reflection mode. We choose the frequency-shift method to be analyzed because its advantage in a computational viewpoint. The simple filtered backprojection algorithm was implemented to reconstruct the tomographic images of the soft tissue suffered by bone. The results are shown the successful of this method over the transmission mode tomography. Also the simulations for noisy data were analyzed. © 2006 IEEE.